Tantangan Pengarsipan Seni Pertunjukan di Institut Seni Indonesia (ISI) Surakarta - Jamal, Jamal (Khazanah: Jurnal Pengembangan Kearsipan, 2024)
This research aims to do a theoretical study for recognizing the challenges related to archivingperforming arts at the Indonesian Institute of the Arts (ISI) Surakarta as an integral component of the development of the ISI Surakarta Arts Archive. Employing qualitative research methods with a literature review approach, it gathered information from various sources such as books, academic journals, and previous research. Data analysis is carried out by describing and interpreting the diverse viewpoints and procedural aspects. This research uncovers a fundamental challenge in archiving performing arts at ISI Surakarta due to their ephemeral nature—these arts exist solely during live performances, making preservation a complex task. Tracking the existence of performing arts relies on annotations, recordings, and documents that serve as historical records of these live events. The annotations, recordings, and documentsare derived from the artist's creative process, performance management, audience feedback, artcritics, and public reception. The results of the research state that the challenges faced in archiving performing arts at ISI Surakarta include (1) the need to enhance archivists' understanding of the genesis of performing arts to trace and compile performance-relatedannotations/recordings effectively; (2) the importance of cultivating archival literacy among artists to grasp better and acknowledge the significance of documenting the creative process of their artistic works throughout production and post-performance phases; and (3) the necessity of developing an interactive digital archive for performing arts to draw the artists, the public, and users an access right to contribute authentic and pertinent records, documents, and documentation associated with specific performing arts.